Overview of viruses of legumes other than groundnut in Africa - Hughes, J.; Shoyinka, S.A. (2003)
Many legume species are grown in sub-Saharan Africa (SSA). In addition to groundnut (Arachis hypogaea L.), which has a major production area in West Africa, Cicer arietinum L. (chickpea), Glycine max (L.) Merr. (soybean), Vigna unguiculata (L.) Walp. (cowpea), Phaseolus spp. (bean), and Cajanus cajan (L.) Millsp. (pigeon pea) are widely grown in sub-Saharan Africa (Allen and Lenné 1998). The yield of these crops from sub-Saharan Africa in 2001 is given in Table 1 and, while it reflects the relative importance of the crops in the region, it must be noted that some crops are restricted to more limited areas where they may be of significant local importance. The most important viruses infecting the individual crops, diagnosis, and methods of control, are discussed.